Developing a Robust Disaster Response Robot: CHIMP and the Robotics Challenge. Issue 2 (March 2017) - Haynes, G. Clark; Stager, David; Stentz, Anthony; Vande Weghe, J. Michael; Zajac, Brian; Herman, Herman; Kelly, Alonzo; Meyhofer, Eric; Anderson, Dean; Bennington, Dane; Brindza, Jordan; Butterworth, David; et al.
Abstract : CHIMP, the CMU Highly Intelligent Mobile Platform, is a humanoid robot capable of executing complex tasks in dangerous, degraded, human‐engineered environments, such as those found in disaster response scenarios. CHIMP is uniquely designed for mobile manipulation in challenging environments, as the robot performs manipulation tasks using an upright posture, yet it uses more stable prostrate postures for mobility through difficult terrain. In this paper, we report on the improvements made to CHIMP—both in its mechanical design and its software systems—in preparation for the DARPA Robotics Challenge Finals in June 2015. These include details on CHIMP's novel mechanical design, actuation systems, robust construction, all‐terrain mobility, supervised autonomy approach, and unique user interfaces utilized for the challenge. Additionally, we provide an overview of CHIMP's performance, and we detail the various lessons learned over the course of the challenge. CHIMP was one of the winners of the DARPA Robotics Challenge, completing all tasks and finishing in 3rd place out of 23 teams. Notably, CHIMP was the only robot to stand back up after accidentally falling over, a testament to the robustness engineered into the robot and a remote operator's ability to execute complex tasks using a highly capable robot. We present CHIMP as a concrete engineering example of a successful disaster response robot.